Innovation in the realm of the unforeseen: a review of competence needed - Torgersen, Glenn-Egil; Boe, Ole; Magnussen, Leif Inge; Olsen, Dorothy Sutherland; Scordato, Lisa (Frontiers in Psychology, 2024)
Introduction Our main research question in this article was: What are the competence structures for innovative processes? Both the nature of the unforeseen and innovation are related to something unknown, i.e., that competence needs to be developed to be able to handle situations and solutions that are not yet completely known. In our article, we address the question of how studies of innovation describe and use concepts of competence in various forms. Method We performed a systematic review of the relation between the unforeseen and innovation. In this systematic review we followed the Non-Interventional, Reproducible, and Open (NIRO) Systematic Reviews protocol. The identification of studies via databases and registers was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyzes (PRISMA) statement. The various types of competence found in the literature review were grouped in such a way that we could develop a structure to use as the basis for a new concept of competence needed in order to initiate and implement innovative processes. We refer to this overview of different competence types as designated competence structures for innovative processes. The searches resulted in the following number of abstracts, respectively Web of Science (2997), ERIC (454), and PsycInfo (550), meaning that a total of 3,768 abstracts were found to be relevant. The 3,768 abstracts were imported into the program Covidence for screening in the first search. Results After completing the evaluation process in accordance with the PRISMA checklist and flow diagram, 32 abstracts were found to be relevant for our research question as they were related to competence for the unforeseen and innovation. Conclusion Few of the studies we investigated specifically mention competence. Another finding is that the innovation literature describes the activities that should take place linked to what it refers to as competence. Thus, the innovation research field does not define what the competence is or what it consists of, at either individual or group level, but rather describes the activities that contribute to successful innovation in an organization with little emphasis on how this competence should be developed. Training perspectives are lacking when it comes to innovation literature perspectives on competence.